INFLUENCE OF MATERNAL AGE ON PERINATAL RESULTS (Fiep Bulletin - online, 2011)
The increase in the incidence of pregnancy at extremes of reproductive life before the age of 20 and after 35 years-old, is actual. The gestation is associated with physiological and anatomical adjustments, which carry transformations of maternal organism and, the isolated maternal age has already been queried in several studies as a prevailing factor and/or cause of alterations on perinatal results. Thus, we aimed at identifying the influence of maternal age on perinatal results. Information contained in Certificate of Live Birth regarding the year 2007, Cajazeiras town, Paraiba. The variables studied were: duration of pregnancy, kind of birth, number of antenatal consultations realized and weight of new born, all correlated to maternal age. The data were analyzed and statistically codified by Statistical Package for the Social Sciences (SPSS), using the Chi-square test and a 5% significance level for the rejection of nullity hypothesis has been adopted. In a total of 830 DNV observed there was not statistical significance in the variable maternal age over perinatal results. There was prevalence of gestations at term, Caesarian birth, low adhesion to antenatal and ideal weight of new born among most mothers studied. This research provided the observation that maternal age as an isolated factor does not exert influence on perinatal results, so it becomes necessary the assessment of common characteristics in both age groups researched, such as socioeconomic and sociodemographic levels, aiming at observing the responsible correlations, mainly, because of high rates of Caesarian births and low adhesion to antenatal in the group studied. We conclude that in a local level, pregnant adolescents and adults possibly submitted to the same socioeconomic conditions and antenatal assistance presented similar perinatal results in both the variables researched.
Keywords: Certificate of Live Birth; Maternal age; Perinatal results